Occupational asthma as a differential diagnosis of adult-onset asthma – a case report - Devaraj, Navin Kumar; Abdul Rashid, Aneesa; Shamsuddin, Nurainul Hana; Abdullah, Ahmad Afifuddin; Tan, Chun Han; Chow, Zhen Yee (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Bronchial asthma causes great morbidity and mortality worldwide. Certain occupations especially those exposed to known triggers of asthma such as animal fur, dusts or solvents may trigger asthma attacks in a previously undiagnosed individual or worsen its’ control in a known asthmatic. This is especially true for adult-onset asthma. This may in turn the health of the affected workers and affect their productivity. Affected workers may be given job reassignment and eligible for medical compensation from Social Security Organisation (SOSCO). This case report will look at how two individuals in very distinct occupation were diagnosed with suspected occupational asthma.